2019
DOI: 10.1038/s41398-019-0491-9
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor as a possible predictor of electroconvulsive therapy outcome

Abstract: While brain-derived neurotrophic factor (BDNF) has been shown to predict response to pharmacotherapy in depression, studies in electroconvulsive therapy (ECT) are small and report conflicting results. This study assesses the association between pre-treatment BDNF levels and ECT outcome in severe late-life unipolar depression (LLD). The potential of BDNF as a clinical predictor of ECT outcome was subsequently evaluated. Characteristics associated with low and high BDNF subgroups were determined as well. Ninety-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Numerous studies have investigated the effect of ECT on serum levels of BDNF in patients with MDD. 22,[28][29][30][31][32][33] Consistent with our findings, earlier studies also found that ECT could not alter serum levels of BDNF, despite decreasing depression severity. [28][29][30][31]33,34 This indicates that ECT probably does not share a common mechanism of action as antidepressants in the improvement of depressive symptoms for patients with TRD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Numerous studies have investigated the effect of ECT on serum levels of BDNF in patients with MDD. 22,[28][29][30][31][32][33] Consistent with our findings, earlier studies also found that ECT could not alter serum levels of BDNF, despite decreasing depression severity. [28][29][30][31]33,34 This indicates that ECT probably does not share a common mechanism of action as antidepressants in the improvement of depressive symptoms for patients with TRD.…”
Section: Discussionsupporting
confidence: 92%
“…A perennial question among researchers is whether it is more correct to measure BDNF levels in plasma, serum or whole blood. BDNF is known to be stored in human platelets and to circulate in plasma, 22 but BDNF concentration in plasma is affected by the handling of the blood sample, and it is released upon platelet degranulation. Thus, circulating BDNF is usually measured in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to nonconvulsive electrotherapy (NET) using standard ECT technique but below seizure threshold, the change in serum BDNF levels in patients with TRD was not correlated with the antidepressant effects of NET ( Zheng et al, 2020 ). A recent study concluded that serum BDNF levels in patients with late-life unipolar depression cannot be considered an eligible biomarker for the antidepressant effects of ECT ( Van Zutphen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent works have shown that not all antidepressants increase BDNF concentrations ( 47 ), and antidepressant-induced rise in BDNF concentrations are more substantial in responders compared to non-responders ( 48 51 ). Moreover, it was demonstrated that high-intensity exercises ( 52 ), electroconvulsive therapy ( 15 , 18 , 19 , 53 ), and deep brain stimulation ( 54 ) also increase BDNF levels. In animal studies, it has been revealed that vortioxetine enhances the behaviors of depressed rodents probably by influencing the cAMP/CREB/BDNF signal pathway and promoting the expression of BDNF in the dorsal and ventral hippocampus of the animals ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%